Meningkatkan Keterampilan Berfikir Kritis Menggunakan Model MEANING GREAT Dengan Media Animasi Berbasis Interaktif Pada Mata Pelajaran IPAS Siswa Kelas IV SDN Kebun Bunga 4 Banjarmasin. - Diky Raihan Akbar; Akhmad Riandy Agusta; Fathul Jannah; Wahdah refia Rafianti (CV. ITTC INDONESIA, 2025)
This research identifies the low activity and critical thinking skills of students in IPAS learning, caused by methods that are less focused on students and monotonous learning. To overcome this problem, the MEANING GREAT learning model was applied. The aim was to describe the improvement of learning quality, student activity, as well as critical thinking skills and student learning outcomes. This research used the Classroom Action Research (PTK) method with the subject of 21 fourth grade students of SDN Kebun Bunga 4 Banjarmasin, conducted in three meetings. Data were collected through qualitative observation and quantitative written tests. The results showed an increase in teacher activity from a score of 33 to 39, student activity from 52% to 90%, critical thinking skills from 48% to 90%, and the completeness of student learning outcomes from 76% to 90%. The MEANING GREAT model proved effective in improving the quality of learning and can be an alternative for teachers to improve students' critical thinking skills.